Recent developments of protein kinase inhibitors as potential AD therapeutics - Hilgeroth, Andreas; Tell, Volkmar (Frontiers in Cellular Neuroscience, 2013)
Present AD therapies suffer from inefficient effects on AD symptoms like memory or cognition, especially in later states of the disease. Used acteylcholine esterase (ACE) inhibitors or the NMDA receptor antagonist memantine address one target structure which is involved in a complex, multifactorial disease progression. So the benefit for patients is presently poor. A more close insight in the AD progression identified more suggested target structures for drug development. Strategies of AD drug development concentrate on novel target structures combined with the established ones dedicated for combined therapy regimes, preferably by the use of one drug which may address two target structures. Protein kinases have been identified as promising target structures because they are involved in AD progression pathways like pathophysiological tau protein phosphorylations and amyloid β toxicity. The review article will shortly view early inhibitors of single protein kinases like glycogen synthase kinase (gsk3) β and cyclin dependent kinase 5. Novel inhibitors will be discussed which address novel AD relevant protein kinases like dual-specifity tyrosine phosphorylation regulated kinase 1A (DYRK1A). Moreover, multitargeting inhibitors will be presented which target several protein kinases and those which are suspected in influencing other AD relevant processes. Such a multitargeting is the most promising strategy to effectively hamper the multifactorial disease progression and thus gives perspective hopes for a future better patient benefit.